T13. CORNEAL CONFOCAL MICROSCOPY DETECTS NEURAL CHANGES IN SCHIZOPHRENIA. (18th May 2020) - Woodruff, Peter; Ponirakis, Georgios; Ghandi, Reem; Hussein, Amani; Bhagat, Anjushri; Petropoulos, Ioannis; Khan, Adnan; Gad, Hoda; Aly Al Sotouhy, Ahmed; Own, Ahmed; Vattoth, Surjith; Ramadan, Marwan; et al.
Abstract: Background: A combination of neurodevelopmental and degenerative neural changes are likely to underpin positive and negative symptoms in schizophrenia. However, there are currently no validated biomarkers to accurately quantify the extent of neural changes in schizophrenia. Corneal confocal microscopy (CCM) is a non-invasive ophthalmic imaging technique that has been used to demonstrate in vivo corneal nerve fiber abnormalities in a range of peripheral neuropathies and central neurodegenerative disorders including Parkinson's disease, multiple sclerosis and dementia. We wished to test the hypothesis that corneal nerve abnormalities occur in patients with schizophrenia, particularly those with negative symptoms and cognitive impairment. Methods: Patients with DSM-V schizophrenia without other causes of peripheral neuropathy other than metabolic syndrome underwent assessment of clinical ratings (Positive and Negative Symptoms Scale (PANSS), cognitive function (Montreal Cognitive Assessment (MOCA) and Corneal confocal microscopy (CCM), vibration perception threshold (VPT) and sudomotor function testing. Healthy controls underwent the same assessments apart from PANSS. Results: 55 subjects without (n=38) and with schizophrenia (n=17) with comparable mean age (35.7±8.5 vs 35.6±12.2, P=0.96) were studied. Patients with schizophrenia had significantly higher body weight (93.9±25.5 vs 77.1±10.1, P=0.02) and lower Low Density Lipoproteins (2.6±1.0 vs 3.4±0.7, P=0.02) compared with healthy controls. The proportion of gender, systolic and diastolic blood pressure, HbA1c, cholesterol, triglyceride and High Density Lipoproteins were comparable between the two groups. Patients with schizophrenia had significantly lower corneal nerve fibre density (CNFD, fibers/mm2) (35.6±6.5 vs 23.5±7.8, p<0.0001), branch density (CNBD, branches/mm2) (98.1±30.6 vs 34.4±26.9, p<0.0001), and fibre length (CNFL, mm/mm2) (24.2±3.9 vs 14.3±4.7, p<0.0001) compared with healthy controls but no difference in peripheral neuropathy assessed by VPT and sudomotor function testing. The area under the Receiver Operating Characteristic Curve (95% CI) of CNFD, CNBD, CNFL to distinguish patients with schizophrenia from healthy controls were 87.0% (76.8–98.2%), 93.2% (84.2–102.3%), 93.2% (84.4–102.1%), respectively. Discussion: These preliminary results: support the hypothesis that corneal nerve abnormalities occur in schizophrenia; corneal confocal microscopy has high diagnostic capability to distinguish subjects with schizophrenia from healthy controls; provide evidence to support the potential application of corneal confocal microscopy as a non-invasive technique to detect neural change in schizophrenia.